The shelter recovery trajectory of typhoon Yolanda survivors: A critical synthesis review - Iftekhar Ahmed; Shelley Tuazon Guyton (Progress in Disaster Science)
Typhoon Haiyan (Yolanda) struck the Philippines in 2013 and devastated more than a million houses. To address the devastation, the government and humanitarian agencies undertook a variety of shelter recovery programs. However, there are reports that a large number of people were not supported for their shelter recovery, so questions arise regarding to what extent they managed to recover. The conceptual framework of this paper is framed by two related discourses – the vulnerability paradigm and a pro-poor policy agenda – relevant in the Global South context of the Philippines. The reason for focusing on shelter is because that is the sector which often experiences maximum impact in disasters, as was the case in Yolanda. Shelter recovery is a protracted process, and agencies usually engage over the short term, which is why this paper laid the foundation for future empirical investigations on the conditions on the ground now. There are many challenges in the recovery process, complicated by the government's restrictions on rebuilding near the coast, where nonetheless people built informal settlements to pursue their coastal livelihoods, and are hence vulnerable to future typhoons. Drawbacks of the shelter interventions are explored in relation to poverty, participation, self-recovery, land tenure, urban and rural differences, post-Yolanda cost escalation and links to Water, Sanitation and Hygiene (WASH). It is recommended that people should be supported to build disaster-resilient and durable shelter, drawing on their social capital.